2021
DOI: 10.1155/2021/6637584
|View full text |Cite
|
Sign up to set email alerts
|

Antihypernociceptive and Neuroprotective Effects of the Aqueous and Methanol Stem-Bark Extracts of Nauclea pobeguinii (Rubiaceae) on STZ-Induced Diabetic Neuropathic Pain

Abstract: The greatest common and devastating complication of diabetes is painful neuropathy that can cause hyperalgesia and allodynia. It can disturb psychosocial functioning by increasing levels of anxiety and depression. This work was designed to evaluate the antihyperalgesic, antidepressant, and anxiolytic-like effects of the aqueous and methanol extracts of Nauclea pobeguinii stem-bark in diabetic neuropathy induced by streptozotocin in mice. Diabetic neuropathy was induced in mice by the intraperitoneal administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…A behavioural depressive state is indicated by increase in immobility time displayed by experimental animals in the OFT and FST tests ( Shalam et al, 2007 ). In line with previous studies, we observed that diabetic rats exhibited depressive like behaviour as indicated by increased immobility time in the FST, as well as reduced locomotive activity in the OFT test when compared to the normoglycemic rats ( de Morais et al, 2014 , de Morais et al, 2016 ; Tsafack et al, 2021 ). SiPE administration significantly reduced the immobility time and increased the swimming time as well as the exploratory behaviour in the FST and OFT, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A behavioural depressive state is indicated by increase in immobility time displayed by experimental animals in the OFT and FST tests ( Shalam et al, 2007 ). In line with previous studies, we observed that diabetic rats exhibited depressive like behaviour as indicated by increased immobility time in the FST, as well as reduced locomotive activity in the OFT test when compared to the normoglycemic rats ( de Morais et al, 2014 , de Morais et al, 2016 ; Tsafack et al, 2021 ). SiPE administration significantly reduced the immobility time and increased the swimming time as well as the exploratory behaviour in the FST and OFT, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In fact diabetes and depression have been shown to display a bifacial etiology, as patients suffering from depression have a higher risk of developing T2DM due to the activation of several pathways that can initiate insulin resistance (Champaneri et al, 2010;Deischinger et al, 2020). In addition, previous studies have illustrated that anxiety and depression are characteristic features associated with diabetic neuropathy (Mbiantcha et al, 2019;Tsafack et al, 2021). FST and OFT are the most commonly used behavioural studies for evaluating antidepressant activity of pharmacological agents (Dulawa et al, 2004;Cryan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has reportedly been useful in the treatment of jaundice, gonorrhea, fever, stomach ache, and epilepsy (Njoya et al, 2017). In Cameroon, the plant is used in the management of hyperglycemia, articular pain, stomach pains, and inflammation (Tsafack et al, 2021). Anti-helminthic application of stem bark water decoction of N. diderrichi and N. pobeguinii were also reported in Congo while its anti-malaria activity was recorded in Mali (Haudecoeur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%